Mixed convection boundary layer flow about an isothermal sphere in a micropolar fluid - Nazar, Roslinda; Amin, Norsarahaida; Pop, Ioan (Elsevier SAS., 2003)
The steady mixed convection boundary layer flow of a micropolar fluid about a sphere with a constant surface temperature is considered for both the assisting and opposing flow cases. The transformed conservation equations of the non-similar boundary layers are solved numerically using a very efficient finite-difference method known as the Keller-box scheme. Numerical results are presented for different values of the material and mixed convection parameters K and Î», respectively, and with the Prandtl number Pr = 0.7 and 7. It is found that assisting flow (Î» > 0) delays separation of the boundary layer and can, if the assisting flow is strong enough, suppress it completely. The opposing flow (Î»<0), on the other hand, brings the separation point nearer to the lower stagnation point of the sphere and for sufficiently strong opposing flows there will not be a boundary layer on the sphere. Some results were given in the form of tables. Such tables are very important and they can serve as a reference against which other exact or approximate solutions can be compared in the future